Two works of Central American camara music - Meza Sandoval, Gerardo E. (2025)
To celebrate sixty years since its premiere, two works by Central American composers Jorge Sarmientos and Benjamín Gutiérrez will be discussed, Sexteto No 2 op. 35 and Música para siete instrumentistas respectively. After a musical analysis and description of the chosen works, the dodecaphonic treatment has been demonstrated in both compositions. We observe that the treatment given with this composition technique is an important mark in Central American musical composition at a certain time. We say that they are a milestone, due to their dimensions, treatment, development, handling of materials that mark a step ahead of their predecessors. Neither of the two compositions has crossed the threshold of canonization and they are ignored in the repertoires of chamber groups in the region. With this work we want to draw attention to them and motivate the approach to this material from the Central American heritage.